Reclaiming Human-Centered Education: Muhammadiyah's Progressive Islamic Response to Smart Society 5.0 - Muh Khairul Azmi; Triono Ali Mustofa (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
The concept of Smart Society 5.0 developed in Japan emphasizes a human-centered approach through the integration of digital technology, artificial intelligence, the Internet of Things, and big data to improve social well-being in a sustainable manner. However, this transformation also has serious implications for the world of education, especially related to the potential for dehumanization of learning, the tendency to secularize science, and the inequality of access to education due to the digital divide. This research aims to analyze the strategic position of Muhammadiyah education in facing the dynamics of Smart Society 5.0 and formulate the response of Progressive Islamic Education to these challenges. This research uses a literature study method with a qualitative-descriptive approach through the analysis of scientific literature and official documents of Muhammadiyah published in the range of 2018–2024. The results of the study show that Muhammadiyah responds to the challenges of Society 5.0 through a value-based education paradigm by placing technology under the control of the principle of monotheism, strengthening humanist pedagogy in the relationship between teachers and students, and revitalizing Al-Ma'un theology as the basis of social justice and educational inclusivity. This finding confirms that Muhammadiyah education is not only technologically adapted, but plays an active role as a moral guide so that the transformation of education in the era of Society 5.0 remains oriented towards humanity and social justice.